Dynamic Controllability with Overlapping targets: A Generalization of the Tinbergen-Nash Theory of Economic Policy - Giovanni Di Bartolomeo; Nicola Acocella; Andrew Hughes Hallett (Fondazione Eni Enrico Mattei (FEEM), 2005)
We generalize some recent results developed in static policy games with multiple players, to a dynamic context. We find that the classical theory of economic policy can be usefully applied to a strategic context of difference games: if one player satisfies the Golden Rule, then either all other players policies are ineffective with respect to the dynamic target variables shared with that player; or no Nash Feedback Equilibrium can exist, unless they all share target values for those variables. We extend those results to the case where there are also non-dynamic targets, to show that policy effectiveness (a Nash equilibrium) can continue to exist if some players satisfy the Golden Rule but target values differ between players in the non-dynamic targets. We demonstrate the practical importance of these results by showing how policy effectiveness (a policy equilibrium) can appear or disappear with small variations in the expectations process or policy rule in a widely used model of monetary policy.
Keywords: C72; E52; E61; 330; Policy games; Policy ineffectiveness; Static controllability; Existence of equilibria; Nash feedback equilibrium; Spieltheorie; Wirtschaftspolitik; Gleichgewicht; Nash-Gleichgewicht; Theorie